LUNA measurement found no evidence of a low-energy resonance in 6Li(p, γ)7Be reaction - Piatti D. (EPJ Web of Conferences, 2023)
The 6Li(p, γ)7Be reaction is mainly at work in three nucleosynthesis scenarios: Big Bang Nucleosynthesis, 6Li depletion in pre-main and in main sequence stars and cosmic ray interaction with interstellar matter. The 6Li(p, γ)7Be S-factor trend was poorly constrained at astrophysical energies because of conflicting experimental results reported in literature. A recent direct measurement, indeed, found a resonance-like structure at Ec.m. = 195 keV, corresponding to an excited state at Ex ∼ 5800 keV in 7Be which, however, has not been confirmed by either other direct measurements or predicted by theoretical calculations. In order to clarify the existence of this resonance, a new experiment was performed at the Laboratory for Underground Nuclear Astrophysics (LUNA), located deep underground in Gran Sasso Laboratory. Thanks to the extremely low background environment, the 6Li(p, γ)7Be cross section was measured in the center-of-mass energy range E = 60-350 keV with unprecedented sensitivity. No evidence for the alleged resonance was found. LUNA results was confirmed by latest published indirect determination of 6Li(p, γ)7Be S-factor and it is supported by a recent theoretical study.